ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH - Fera Estiana, 15.05.52.0160; Maryono, Maryono (Students' Journal of Accounting and Banking, 2019)
This study aims to examine and analyze the analysis of factors that influence the level of disclosure of District/City Government Financial Statements in the province of Central Java. The independent variables of this study are PAD, total assets, total SKPD, independence ratio, and audit findings on the level of disclosure of Regenc /City LKPD in Central Java Province. The population of this study is the Regency/City in Central Java Province during the 2015-2017 budget year which was audited by the BPK. The sample used was 105 local government financial statements using the census method in other words all populations were sampled. The method of data analysis in this study uses multiple regression with SPSS 19. The results of hypothesis testing indicate that PAD has a significant positive effect on the level of disclosure of LKPD, total assets have a significant positive effect on the level of disclosure of LKPD, total SKPD has a positive and insignificant effect, the independence ratio has a positive but not significant effect, and audit findings have a positive but not significant effect.